A low-cost, high-speed, multi-channel Arduino-based data acquisition system for wind turbine systems. Issue 5 (October 2020) - Bradney, David; Evans, Samuel; Chu, Mu; Clausen, Philip
Commercially available high-speed multi-channel data acquisition systems can be expensive to purchase and are generally difficult to tailor to specific applications. Arduino is an open-source prototyping platform that facilitates the design and build of computer controlled systems for a wide variety of uses. This article describes in detail several separate high-speed data acquisition systems that have been integrated to simultaneously acquire data from sensors on the rotor, platform and tower of an operating 5 kW horizontal-axis wind turbine along with wind speed and direction data. Due to the presence of strong magnetic fields at the turbine site, turbine direction and yaw rate were measured using high-definition visual footage from a GoPro ® and analysed in a MATLAB script. The processed data from the GoPro system was time-aligned with data from the Arduino-based systems allowing the response of the turbine to be analysed in detail.